Estudo do comportamento mecânico em soldas do aço inoxidável lean duplex UNS S32304 utilizando modelos de encruamento - Caetano, Gabriela Aksascki (2023)
Duplex stainless steels are characterized by their weldability, corrosion resistance, and good mechanical properties, the latter two properties being due to their biphasic microstructure of ferrite and austenite. The main focus of this research was to investigate the stress-strain behavior using work hardening models of the lean duplex stainless steel UNS S32304 with a thickness of 1.8 mm, welded by autogenous TIG process followed by heat treatment at different temperatures. In addition, initial investigations were carried out with laser beam welding using powder of duplex steel with TiB2 dispersion as a filler material. Microhardness tests, metallographic characterization with stereoscopy, optical and scanning electron microscopy, tensile test, and phase quantification by image processing were performed to evaluate the specimens welded by autogenous TIG process. The metallographic analysis showed that the heat treatments after TIG welding promoted an increase in the austenite phase content. An analysis of the stress-strain curves using work hardening models showed that the Voce and Hockett-Sherby models presented goodness-of-fit with the experimental data. In addition to the research, it was demonstrated that the parameters of both models are correlated with the volumetric content of austenitic phase in the fusion zone. Furthermore, laser beam welding with powder as filler material showed complete penetration, complete melting of the powder and the sheet, and no porosity was detected. It was verified through instrumented indentation measurements the dispersion of TiB2 and increased hardness and mechanical strength of the weld.